2016
DOI: 10.1016/j.wjorl.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

mTOR, metabolism, and the immune response in HPV‐positive head and neck squamous cell cancer

Abstract: Extensive preclinical studies have identified mammalian target of rapamycin (mTOR) activation as a frequent molecular signature underlying head and neck squamous cell carcinoma (HNSCC), including the distinct clinical subtype that is human papillomavirus (HPV) related, and have demonstrated the potential therapeutic utility of mTOR inhibitors in the treatment of these cancers. Numerous clinical studies have begun to evaluate this potential, however few have selected for and fewer have focused specifically on H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Many of the previous findings of tumor-induced neuroinflammation were obtained in model systems that are highly cachectic (Braun et al, 2011; Norden et al, 2015; Ropelle et al, 2007). Despite the lack of cachexia our HPV+ tumor model has a highly inflammatory nature, which aligns with the highly metabolic profile of the HPV+ tumor (Coppock and Lee, 2016; Coppock et al, 2016), in agreement with what is observed in HPV-related head and neck cancer (Krupar et al, 2014). A final advantage of our current model system is that the tumor responds to a regimen of cisplatin-based chemoradiation that is similar to the treatment regimen employed in patient populations.…”
Section: Discussionsupporting
confidence: 87%
“…Many of the previous findings of tumor-induced neuroinflammation were obtained in model systems that are highly cachectic (Braun et al, 2011; Norden et al, 2015; Ropelle et al, 2007). Despite the lack of cachexia our HPV+ tumor model has a highly inflammatory nature, which aligns with the highly metabolic profile of the HPV+ tumor (Coppock and Lee, 2016; Coppock et al, 2016), in agreement with what is observed in HPV-related head and neck cancer (Krupar et al, 2014). A final advantage of our current model system is that the tumor responds to a regimen of cisplatin-based chemoradiation that is similar to the treatment regimen employed in patient populations.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, HPV-related OPSCC patients with high raptor and rictor expression tended to have a worse prognosis than those with low or medium expression. Although there have been a number of reports describing mTOR activation in head and neck cancer (7,24,26,27,32), little is known about its role in HPV-related OPSCC (23,25,28,29). This is the first report to reveal the overexpression of raptor and rictor in HPV-related OPSCC.…”
Section: Survival Estimation In Relation To Raptor and Rictor Expressionmentioning
confidence: 75%
“…Of the many signaling pathways related to tumor growth, the phosphoinositide 3-kinase (PI3K)/Akt/mTOR signaling pathway is frequently activated in cervical cancer and HPV-related head and neck squamous cell carcinoma (HNSCC) (23)(24)(25)(26)(27)(28)(29)(30). The administration of rapamycin alone significantly prolonged survival in an HPV-positive HNSCC murine model (28).…”
mentioning
confidence: 99%
“…Glucose is the main energy source for tumor cells and GLUT-1 is a key transporter of extracellular glucose [6,7,29]. GLUT-1 is overexpressed in many cancers, including laryngeal carcinoma, and is associated with their metastasis, drug resistance, and prognosis [6,7,[30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%